Assesment of existing calophylum sp. and agathis borneensis regenarations in local village tree planting program - Darma, Yusop. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Both bindang and bintangor trees are timber tree species which are from the araucareaceae and guttiferae families respectively. These trees are in danger becouse of excess logging activities and the opening of forest for other uses. The assessment of these trees were concentrated on diameter and height. Growth rates of bindang and bintangor in planted fields in Bario, Matang Wild Life Centre, Kubah National Park and Sampadi were examined. Growth data (diameter and height) were recorded for the year 2004, early 2005 and supplement existing informated recorded by the Sarawak Forest Corporation. Growth comparison was made between trees planted in different management types (fertilized against non-fertilized) and topographic characeristics (slope and flat land). There were significant differences in growth rates recorded on areas with different topographic characteristics. Similarly, growth rates are significant differences in fields with different management practices. Resltlt indicated that both bindang and bintangor growth well on slope area compared on flat land area.